Effects of Marital Status on Material Conditions - Megan Hicks (The Journal of Undergraduate Research, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The purpose of this research was to examine how marital status may affect social stratification, specifically the differences in material conditions between married couples and cohabitating couples as compared to single people. This research is important because rates of marriage are declining at a large rate and rates of cohabitation are steadily increasing. In terms of relating this to social stratification, it is important to identify that factors that are different in these living situations and also identify the material conditions that are affected by it. I also observed how the combination of gender and marital status disadvantages women. Data from this research comes from a longitudinal survey of adult Poles conducted every five years between 1988-2008 on a representative national sample, called POLPAN. Data from the most recent wave in 2008 is observed for the purposes of reviewing the most recent changes in today’s marital status. As a result performing multiple regressions and descriptive statistics, cohabitating couples were found to be more similar to never married, single people in household income per capita, but were the same when comparing them to car ownership and square meters in the home per capita. Also, marital status is positive for disadvantaging women in the aspect that cohabitating women tend to make the most money of all other civil unions. Larger implications for my research would be to observe education attainment as a factor for both hypotheses, also to look at the changing gender roles in today’s civil unions.